Home‐range size and habitat use of European Nightjars Caprimulgus europaeus nesting in a complex plantation‐forest landscape. (2nd March 2015) - Sharps, Katrina; Henderson, Ian; Conway, Greg; Armour‐Chelu, Neal; Dolman, Paul M.
Abstract : In Europe, the consequences of commercial plantation management for birds of conservation concern are poorly understood. The European Nightjar Caprimulgus europaeus is a species of conservation concern across Europe due to population depletion through habitat loss. Pine plantation‐forest is now a key Nightjar nesting habitat, particularly in northwestern Europe, and increased understanding of foraging habitat selection is required. We radiotracked 31 Nightjars in an extensive (185‐km 2 ) complex conifer plantation landscape in 2009 and 2010. Home‐range 95% kernels for females, paired males and unpaired males were an order of magnitude larger than song territories of paired males, emphasizing the importance of habitats beyond the song territory. Nightjars travelled a mean maximum distance of 747 m from the territory centre each night. Home‐range placement relative to landscape composition was examined by compositional analysis. Pre‐closure canopy forest (aged 5–10 years) was selected at all scales (MCP, 95% and 50% kernels), with newly planted forest (aged 0–4 years) also selected within 50% kernels. For telemetry fixes relative to habitat composition within 2 km of their territory centre, individuals again selected pre‐closure and newly planted forest, and also grazed grass heath. Open ungrazed habitat was not selected, with implications for open habitat planning for biodiversity conservation within public‐owned forests. Despite the Nightjars' selection for younger growth, moth biomass was greater in older forest stands, suggesting that foraging site selection reflects ease of prey capture rather than prey abundance. Within large plantation‐forest landscapes, a variety of growth stages is important for this species and our results suggest that grazing of open habitats within and adjacent to forest will additionally benefit the European Nightjar.